Assessment of written competence in the context of the Cambridge English Preliminary Test B1: Systematic review - Calles Jiménez, Romel Francisco; Moreno Novillo, Ángela Cecibel; Báez Báez, José Antonio; Flores Galeano, Jennifer Karina (Revista de Ciencias Sociales, 2026)
The assessment of writing skills in standardized English exams, such as the Cambridge English Preliminary Test (PTT) at level B1, is fundamental for measuring candidates› communicative ability in this skill. This article presents a systematic review of the assessment criteria applied in the written section of this exam. It considers points related to the different bands that make up the assessment rubric and the weighting that candidates can obtain by fitting into each band. With this approach, a descriptive analysis is carried out on the different elements assessed by official examiners, revealing a deeper understanding of the composition of the assessment criteria for writing skills in individuals with a B1 level of international English. The results clearly indicate each of the points to consider for optimizing the training and assessment process for candidates taking this test. The article concludes that this test provides a powerful feedback tool for practice in simulations and classroom exercises, focusing on content, communicative achievement, organization, and language use.